ZEITLUPE Promotes ABA-Induced Stomatal Closure in Arabidopsis and Populus - Jurca, Manuela; Sjölander, Johan; Ibáñez, Cristian; Matrosova, Anastasia; Johansson, Mikael; Kozarewa, Iwanka; Takata, Naoki; Bakó, Laszlo; Webb, Alex A. R.; Israelsson-Nordström, Maria; Eriksson, Maria E. (Frontiers in Plant Science, 2022)
Plants balance water availability with gas exchange and photosynthesis by controlling stomatal aperture. This control is regulated in part by the circadian clock, but it remains unclear how signalling pathways of daily rhythms are integrated into stress responses. The serine/threonine protein kinase OPEN STOMATA 1 (OST1) contributes to the regulation of stomatal closure via activation of S-type anion channels. OST1 also mediates gene regulation in response to ABA/drought stress. We show that ZEITLUPE (ZTL), a photoreceptor and clock component also regulates ABA-induced stomatal closure in Arabidopsis thaliana, establishing a link between clock and ABA signalling pathways. ZTL sustains expression of OST1 and ABA-signalling genes. Stomatal closure in response to ABA is reduced in ztl mutants, which maintain wider stomatal apertures and show higher rates of gas exchange and water loss than wild-type plants. Detached rosette leaf assays revealed a stronger water loss phenotype in ztl-3; ost1-3 double mutants, indicating that ZTL and OST1 contributed synergistically to the control of stomatal aperture. Experimental studies of Populus sp., revealed that ZTL regulated the circadian clock and stomata, indicating ZTL function was similar in these trees and Arabidopsis. PSEUDO-RESPONSE REGULATOR 5 (PRR5), a known target of ZTL, affects ABA-induced responses, including stomatal regulation. Like ZTL, PRR5 interacted physically with OST1 and contributed to the integration of ABA responses with circadian clock signalling. This suggests a novel mechanism whereby the PRR proteins – which are expressed from dawn to dusk – interact with OST1 to mediate ABA-dependent plant responses to reduce water loss in time of stress.